2021
DOI: 10.3390/agriculture11121256
|View full text |Cite
|
Sign up to set email alerts
|

Control Potentials of Three Entomopathogenic Bacterial Isolates for the Carob Moth, Ectomyelois ceratoniae (Lepidoptera: Pyralidae) in Pomegranates

Abstract: Ectomyelois ceratoniae (Lepidoptera: Pyralidae) is the primary pest of pomegranates in Saudi Arabia and is mostly controlled using broad-spectrum pesticides. Providing environmentally sound choices to limit reliance on chemical management is a major challenge in the control of E. ceratoniae and, as a consequence, in the protection of pomegranate crops from its invasion. Entomopathogenic bacteria (EPB) symbiotically associated with entomopathogenic nematodes (EPNs) are well-known biocontrol agents of soil-dwell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
3
6
0
Order By: Relevance
“…Five bacterial isolates associated with EPN S. feltiae were identified. These findings are consistent with and add to those previously reported by ( Alotaibi et al, 2021 and Noureldeen et al, 2022 ), who isolated Xenorhabdus sp. and Photorhabdus sp.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Five bacterial isolates associated with EPN S. feltiae were identified. These findings are consistent with and add to those previously reported by ( Alotaibi et al, 2021 and Noureldeen et al, 2022 ), who isolated Xenorhabdus sp. and Photorhabdus sp.…”
Section: Discussionsupporting
confidence: 93%
“…S. tumulicola isolate either cells or filtrates, showed aphicidal activity against A. punicae and A. illinoisensis systematically or through direct contact, causing lethality to the adult stage of both aphid species, and the accumulative mortality approached 100% 48 h following treatment. These results were in accordance with those of ( Alotaibi et al, 2021 ) who observed that the two Xenorhabdus bacterial species EMA and EMC causing significant higher E. ceratoniae larvae mortality than that caused by the Photorhabdus species TT01. In a recent study conducted by Elbrense et al, (2021) , it was discovered that H. bacteriophora and its symbiont, Photorhabdus sp., were more virulent against Pieris rapae and Pentodon algerinus .…”
Section: Discussionsupporting
confidence: 93%
“…on V. livia and E. ceratoniae larvae. These results are consistent with those of Alotaibi et al [ 48 ], who recorded that mortality of E. ceratoniae larvae caused by two Xenorhabdus bacterial species was significantly higher than that of Photorhabdus species. In contrast, a recent study by Elbrense et al [ 15 ] showed that H. bacteriophora and its symbiont, Photorhabdus sp., were more virulent than S. riobravis and its symbiont, Xenorhabdus sp.…”
Section: Discussionsupporting
confidence: 93%
“…Following methods by Alotaibi et al [ 48 ], pomegranate butterfly ( V. livia ) and carob moth ( E. ceratoniae ) larvae were collected from commercial pomegranate orchards located in Taif, Saudi Arabia, and then reared on a wheat bran diet (300 g of wheat bran, 50 g of sugar, 120 mL of water, 130 mL of glycerol, and 9 g of yeast), whereas adults were fed with a 10% honey–water solution. The rearing room was adjusted to 25 ± 1 °C, a relative humidity of 60% and a light–dark cycle of 16 L:8 D.…”
Section: Methodsmentioning
confidence: 99%
“…A successful symbiotic complex needs to be able to kill the available insect prey more efficiently than other alternatives. For this, the EPB should produce toxins [ 87 , 88 , 89 , 90 , 91 ].…”
Section: Coevolution and Co-speciation Of Epn/epb Symbiotic Associationsmentioning
confidence: 99%